2021
DOI: 10.14336/ad.2020.0912
|View full text |Cite
|
Sign up to set email alerts
|

Iron Accumulation and Lipid Peroxidation in the Aging Retina: Implication of Ferroptosis in Age-Related Macular Degeneration

Abstract: Iron is an essential component in many biological processes in the human body. It is critical for the visual phototransduction cascade in the retina. However, excess iron can be toxic. Iron accumulation and reduced efficiency of intracellular antioxidative defense systems predispose the aging retina to oxidative stress-induced cell death. Age-related macular degeneration (AMD) is characterized by retinal iron accumulation and lipid peroxidation. The mechanisms underlying AMD include oxidative stress-mediated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 278 publications
(437 reference statements)
0
52
0
Order By: Relevance
“…[33][34][35][36][37] Iron levels increase in RPE during ageing, which may contribute to ARMD as an important source of oxidative stress. [9][10][11] The increase of intracellular ferrous iron produces hydroxyl and lipid alkoxyl radicals through the Fenton reaction, which causes lipid peroxidation, membrane damage and cell death. 12,13 First, before testing the potential efficiency of a CIT treatment, we assessed its toxicity towards RPE cells.…”
Section: Cit Reduces Cell Death In Oxidative Stressed Rpe Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…[33][34][35][36][37] Iron levels increase in RPE during ageing, which may contribute to ARMD as an important source of oxidative stress. [9][10][11] The increase of intracellular ferrous iron produces hydroxyl and lipid alkoxyl radicals through the Fenton reaction, which causes lipid peroxidation, membrane damage and cell death. 12,13 First, before testing the potential efficiency of a CIT treatment, we assessed its toxicity towards RPE cells.…”
Section: Cit Reduces Cell Death In Oxidative Stressed Rpe Cellsmentioning
confidence: 99%
“…This oxidant is also produced by the photo‐excited lipofuscin that accumulates with age in the RPE, and its accumulation is associated with ARMD 8 . Also, it has been reported that iron levels increase in RPE during ageing and that age‐dependent iron accumulation is accelerated in patients with ARMD 9–11 . Additionally, accumulation of iron can be toxic to the RPE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gain of function variants for RNF13 have been associated with severe neurodegeneration leading to congenital microcephaly, epileptic encephalopathy, and cortical blindness 89 . CRYZ is induced under oxidative stress 54 and detoxification of lipid peroxidation products 55 , both molecular events already implicated in AMD pathogenesis [90][91][92] . Recent GWAS have identified CRYZ as a susceptibility gene for insulin resistance 93 and amyotrophic lateral sclerosis 94 .…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation refers to the lipid oxidative degradation reaction in which lipids lose hydrogen atoms under the action of free radicals or lipid peroxidase, resulting in the oxidation, fracture and shortening of lipid carbon chain, and produce cytotoxic substances resulting in cell damage ( Ayala et al, 2014 ). More and more studies have shown that lipid peroxide is a key mediator of many pathological states, including inflammation ( Kang and Yang, 2020 ), cancer ( Rodríguez-García et al, 2020 ) and neurodegenerative diseases ( Zhao et al, 2021 ). Among them, lipid peroxides have toxic effects on cells mainly through two mechanisms: at the molecular level, lipid peroxides are further decomposed into active substances, which consume nucleic acids and proteins, leading to ferroptosis; at the structural level, lipid peroxidation leads to thinning and increased bending of the biofilm, which ultimately leads to membrane instability and micellar formation ( Gaschler and Stockwell, 2017 ).…”
Section: Ferroptosismentioning
confidence: 99%